2023
DOI: 10.3389/fendo.2023.1272200
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte telomere length is associated with increased risk of endometriosis: a bidirectional two-sample Mendelian randomization study

Chenxue Bai,
Zixiong Shen,
Binxu Qiu
et al.

Abstract: BackgroundEndometriosis (EMs) is a common gynecological disorder. Observational studies on the relationship between leukocyte telomere length (LTL) and EMs have shown conflicting results. The purpose of this study was to evaluate the precise causal relationship between LTL and EMs using Mendelian randomization (MR) methodology.MethodsWe employed MR to assess the causal relationship between LTL and EMs. Summary data from several large-scale genome-wide association studies (GWAS) were used for bidirectional two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…In our research, we addressed these limitations by using MR to probe the causal association between LTL and the incidence of endometriosis. Our study suggests that LTL is a danger element for endometriosis, aligning with previous reports by Bai et al [ 20 ]. However, our subtype analysis revealed that longer LTL specifically increases the risk for only three endometriosis subtypes.…”
Section: Discussionsupporting
confidence: 93%
“…In our research, we addressed these limitations by using MR to probe the causal association between LTL and the incidence of endometriosis. Our study suggests that LTL is a danger element for endometriosis, aligning with previous reports by Bai et al [ 20 ]. However, our subtype analysis revealed that longer LTL specifically increases the risk for only three endometriosis subtypes.…”
Section: Discussionsupporting
confidence: 93%
“…To gauge the IVs strength, we computed the -statistic for each SNP as well as for the entire set of SNPs. The -statistic for a single SNP was calculated using the following formula ( 39 ) , with “ ” representing the impact of the IV on the exposure, and “ ” indicating the standard error of “ .” Meanwhile, the total -statistic followed this formula: , where “ ” stands for the sample size for the exposure, “ ” represents the number of SNPs. The variable “ ” depicts the fraction of exposure variance elucidated by SNPs and is calculated using the formula 2 , where “ ” represents the effect allele frequency of the SNP, and “ ” signifies the SNP’s influence on the exposure.…”
Section: Methodsmentioning
confidence: 99%
“…To gauge the IVs strength, we computed the -statistic for each SNP as well as for the entire set of SNPs. The -statistic for a single SNP was calculated using the following formula 27 , with " " representing the impact of the IV on the exposure, and " " indicating the standard error of " ". Meanwhile, the total -statistic followed this formula: , where " " stands for the sample size for the exposure, " " represents the number of SNPs.…”
Section: Selection Of Ivsmentioning
confidence: 99%